Vision preserving role of radiotherapy in orbital plasmablastic lymphoma (Indian Journal of Case Reports, 2024)
An uncommon but aggressive variant of diffuse large B-cell lymphoma is plasmablastic lymphoma (PBL). Although they primarily involve the gastrointestinal tract, lymph nodes, and oral mucosa of immunocompromised males, orbital presentation is rare. In this article, we report a case of an elderly, immunocompetent gentleman presenting with progressive proptosis, ptosis, and diminished vision of the right eye with a palpable mass in the right upper eyelid. Imaging and biopsy confirmed the rare diagnosis of orbital PBL. After obtaining institutional tumor board concurrence, the patient was delivered 45 Gy external beam radiation therapy followed by six cycles of chemotherapy. Post-therapy, he is in remission with improvement in vision and is currently on maintenance chemotherapy.